Analisis Pola Pengasuhan Anak Broken Home Pasca Perceraian Orang Tua - Enung Nuroniah; Dede Nurul Qomariah (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2025)
The purpose of this study was to analyze the parenting patterns of broken home children after parental divorce. This research uses a qualitative approach. Data collection techniques were conducted through observation, interviews, and documentation studies. Data analysis techniques by reducing data, presenting data and verifying data. The results of the study found that even though the parents were legally separated, the parents still wanted to contribute to the care of their children. The parenting pattern carried out is democratic parenting, where the characteristics are that their children are always encouraged to communicate by parents, controlling children but not rigid, parents lead and direct, parents and children get along well with each other. We also found that divorced parents still want to contribute to parenting. For example, they still maintain their proximity to their children, even though foster parents are busy because of their dual roles.